2022
DOI: 10.1155/2022/5962001
|View full text |Cite
|
Sign up to set email alerts
|

Use and Trends of Diabetes Self-Management Technologies: A Correlation-Based Study

Abstract: Applications and systems for diabetes self-management are growing and involve a vast majority of factors to consider. This study was aimed at examining the integration of portable technologies for diabetes self-management, as well as benefits and issues arising of its use. From a web-based study on several groups of people with diabetes, most of them accustomed to the daily use of devices and applications for self-control, a deeper analysis based on correlations and inference was conducted considering informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The augmentation of knowledge and skills among students in utilising ICT coupled with familial and environmental support, has the potential to significantly amplify the effectiveness of paediatric diabetes management. [16][17][18][19] This research distinguishes itself from previous studies as it focused on exploring the perceptions and utilisation of ICT in managing diabetes in children among Indonesian health students. The researcher's goal was to delve into methodological perspectives and introduce innovative approaches, setting them apart from existing studies.…”
Section: Participantsmentioning
confidence: 99%
“…The augmentation of knowledge and skills among students in utilising ICT coupled with familial and environmental support, has the potential to significantly amplify the effectiveness of paediatric diabetes management. [16][17][18][19] This research distinguishes itself from previous studies as it focused on exploring the perceptions and utilisation of ICT in managing diabetes in children among Indonesian health students. The researcher's goal was to delve into methodological perspectives and introduce innovative approaches, setting them apart from existing studies.…”
Section: Participantsmentioning
confidence: 99%
“…Although it is difficult to estimate the acceptance of digital health in people with type 2 diabetes mellitus (T2DM) for methodological reasons [1], patients have access to a growing number of digital health technologies to support self-management of their condition. A recent study in Italy found that more than 70% of participants use continuous glucose systems [2]. The concept of self-management as an important part of long-term management of chronic diseases is gaining acceptance and it is now considered essential for achieving long-term improvement in health outcomes and quality of life [3].…”
Section: Introductionmentioning
confidence: 99%